Precursor‐driven facile densification of Gd0.1Ce0.9O2−δ interlayer for high‐performance solid oxide fuel cells. (22nd July 2022) - Kim, Seo Ju; Choi, Mingi; Megra, Yonas Tsegaye; Yoo, Hyun Sik; Lee, Jongseo; Suk, Ji Won; Lee, Wonyoung
Summary: The interface between the electrolyte and cathode of solid oxide fuel cells (SOFCs) is essential for determining the electrochemical performance from the sluggish oxygen reduction reaction kinetics and thermal stability from chemical intermixing. In this study, we fabricated a highly densified Gd0.1 Ce0.9 O2− δ (gadolinia doped ceria [GDC]) interlayer between the electrolyte and cathode by introducing additional precursors into the powder suspension inks during spin coating. We verified that these additional precursors facilitated grain growth during the sintering process at a relatively low temperature, resulting in the densification of the GDC interlayer. A densified GDC interlayer‐based anode‐supported cell exhibited a maximum power density of approximately 1.11 W/cm 2 at 650°C, 1.74‐fold greater than that of a conventional GDC interlayer‐based cell, with excellent electrochemical stability for 200 h. Our results demonstrated a simple and cost‐effective process for fabricating highly densified GDC interlayers to develop SOFC with high performance and stability. Abstract : This research investigates a simple and cost‐effective process for fabricating highly densified GDC interlayers to develop SOFC with high performance and stability. Additional GDC precursors facilitated grain growth and increased the density of the Gd0.1 Ce0.9 O2‐δ interlayer. Densified GDC interlayer applied cell exhibited a maximum power density of approximately 1.11 W/cm 2 at 650°C, 1.74‐fold greater than that of a conventional GDC interlayer‐based cell.